Collodion baby: a case report - Kaur, Sumandeep; Kaur, Gurmeet; Rawat, H. C. L.; Sethi, Amanpreet (International Journal of Contemporary Pediatrics, 2018)
Collodion baby is a rare congenital disorder of skin characterized by the presence of extra covering of tough film like membrane which breaks on stretching leading to fissure formation. This condition makes the new-born prone to dehydration, electrolyte imbalance, sepsis and temperature instability leading to frequent complications and high mortality. Here, we present a similar new-born baby born with this condition and presented with severe asphyxia, shock and respiratory failure at birth which was successfully managed in a low resource setting with interdepartmental co-ordination and without the above-mentioned complications.